2004
DOI: 10.1002/neu.20011
|View full text |Cite
|
Sign up to set email alerts
|

GABAB receptor expression and function in olfactory receptor neuron axon growth

Abstract: Neurotransmitters have been implicated in regulating growth cone motility and guidance in the developing nervous system. Anatomical and electrophysiological studies show the presence of functional GABAB receptors on adult olfactory receptor neuron (ORN) nerve terminals. Using antisera against the GABAB R1a/b receptor isoforms we show that developing mouse olfactory receptor neurons express GABAB receptors from embryonic day 14 through to adulthood. GABAB receptors are present on axon growth cones from both dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…In addition, ON terminals express GABA B receptors (Bonino et al 1999;Kratskin et al 2006;Priest and Puche 2004) Koster et al 1999;Maher and Westbrook 2008;Parrish-Aungst et al 2007;Wachowiak and Cohen 1999). Thus ON-evoked PPD can be due to at least two distinct presynaptic mechanisms: reduced vesicle availability and transmitter release due to the high release probability of ON terminals and presynaptic inhibition via activation of GABA B Rs and/or DA D 2 Rs on ON terminals.…”
Section: On-and Et-driven Pg Cells Differentially Regulate Phasic Andmentioning
confidence: 99%
“…In addition, ON terminals express GABA B receptors (Bonino et al 1999;Kratskin et al 2006;Priest and Puche 2004) Koster et al 1999;Maher and Westbrook 2008;Parrish-Aungst et al 2007;Wachowiak and Cohen 1999). Thus ON-evoked PPD can be due to at least two distinct presynaptic mechanisms: reduced vesicle availability and transmitter release due to the high release probability of ON terminals and presynaptic inhibition via activation of GABA B Rs and/or DA D 2 Rs on ON terminals.…”
Section: On-and Et-driven Pg Cells Differentially Regulate Phasic Andmentioning
confidence: 99%
“…Despite the extensive literature on the importance of GABA A R during early development 1,2,6,7,9 , the role of GABA B R has been poorly investigated and data are controversial 10 . For example, a role of GABA B R in neuronal morphological maturation was described in some systems 9,11,12 , but not in others 13 , and only in vitro evidence indicated that GABA B R modulates migration of immature neurons [14][15][16][17] . Furthermore, these in vitro data are in contrast with observations in a number of mouse strains genetically modified for GABA B Rs, which present grossly normal brain and cell morphology [18][19][20][21][22][23][24][25][26] .…”
mentioning
confidence: 99%
“…Glutamate, acting through N-methyl-D-aspartate receptors, induces neurite outgrowth in hippocampal neurons (Mattson et al, 1988) and cerebellar granule cells (Pearce et al, 1987). GABA promotes neurite outgrowth in rat cerebellar neurons (Michler, 1990), rat hippocampal neurons (Barbin et al, 1993), and rat olfactory bulb neurons cocultured with astrocytes (Matsutani and Yamamoto, 1998) via activation of GABA A receptors and of mouse olfactory receptor neurons (Priest and Puche, 2004) via GABA B receptors. Together, these observations strongly suggest that neurotransmitters, including acetylcholine, may play an important role during brain development and, particularly, in neurite outgrowth.…”
mentioning
confidence: 99%